Estrategias de educomunicación para el fortalecimiento en el cuidado del ambiente institucional en la Unidad Educativa 23 de abril, parroquia Santa Fe, año 2023 - Serrano Auquilla, Carlos Miguel (2023)
This study focuses on Educommunication as a strategy for strengthening the institutional environment in an educational establishment. During the data collection phase, as researchers, we identified certain environmental factors that would directly influence the development of teachers and students who are part of this institution. , it should also be noted that interpersonal relationships are conducive to teamwork and communication, in this sense the environmental issue has also been addressed, resulting in a total interest in supporting processes that are aimed at protecting and having the environment. Keywords: Institutional environment, Educommunication, education, communication, environment, interpersonal relationships, strategy.